RUANG TANPA KENDALI: MOBILITAS MAKASSAR DALAM KRISIS - Djufri, Djufri (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
Makassar is currently facing a mobility crisis that is not merely technical, but deeply embedded in the social, political, and spatial dimensions of urban life. Mobility spaces in the city—roads, transport nodes, and travel rhythms—have become contested arenas where technocratic planning collides with residents’ everyday realities. This study aims to examine how mobility spaces in Makassar are produced, negotiated, and lived by urban dwellers amid infrastructural dysfunction and unequal access. Using a qualitative, city-based ethnographic approach, the research was conducted across key mobility corridors and densely populated neighborhoods. Conceptually, this study draws on the frameworks of spatial anarchy (Castells & Smith), temporal disorientation (Zerubavel), and the politics of infrastructure (Larkin) to analyze how disorganized space and time shape citizens’ mobility experiences. Findings reveal that Makassar’s mobility space is marked by spatial fragmentation, erratic urban rhythms, and various forms of micro-resistance—such as the use of informal routes, modifications to pete-pete (minibus) trajectories, and the occupation of street space by informal economic activities. This research contributes theoretically to urban anthropology and the discourse on mobility justice by foregrounding the need to understand cities from below—through the lived experiences of residents who continuously adapt within unruly and unstable urban environments